Financial Reporting and Disclosure terhadap Kualitas Informasi Keuangan: A Systematic Literature Review - Meilan Sri Despitra; Hafidatul Husna; Raifan Wahyu Satria; Rifna Anggraini (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyze the role of financial reporting and disclosure in improving the quality of financial information. Using a descriptive qualitative approach using the Systematic Literature Review (SLR) method, an analysis of 26 international journal articles published between 2020 and 2026 was conducted. The literature selection process referred to the PRISMA guidelines to ensure that the identification, screening, eligibility, and inclusion stages were carried out systematically and transparently. The results show that financial reporting and disclosure generally contribute positively to increasing transparency, reducing information asymmetry, and strengthening investor confidence in financial reports. However, this influence is not always consistent because it is influenced by the quality of disclosure, company characteristics, and applicable regulatory conditions. Furthermore, earnings quality, value relevance, and conservatism have been shown to play a significant role in improving the quality of financial information, although their effectiveness depends on both internal and external factors of the company.